Teoretska praksa v inovacijsko naravnanem raziskovalnem okolju - Breznik, Maja (Primerjalna književnost, 2012)
The political assault on pure science and theoretical production imperils the very foundations of both "soft" and "hard" sciences. What positions are scientists taking towards the changing conditions of research? I will look at the epistemological position and self-reflection in scientific practices, the material conditions of research (particularly publishing and scientific impact measuring), the responses to external demands and the social positioning of science.
Keywords: epistemologija; epistemology; družbene vede; science; znanost; raziskovanje; merjenje vpliva